2017
DOI: 10.1136/acupmed-2016-011176
|View full text |Cite
|
Sign up to set email alerts
|

Manual Acupuncture for Myofascial Pain Syndrome: A Systematic Review and Meta-Analysis

Abstract: Objective To assess the efficacy of manual acupuncture (MA) in the treatment of myofascial pain syndrome (MPS). Methods We searched for randomised controlled trials (RCTs) comparing MA versus sham/placebo or no intervention in patients with MPS in the following databases from inception to January 2016: PubMed; Cochrane Library; Embase; Web of Science; and China Biology Medicine. Two reviewers independently screened the literature extracted data and assessed the quality of the included studies according to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
6

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 39 publications
(34 reference statements)
0
15
0
6
Order By: Relevance
“…A substantial body of evidence demonstrates that acupuncture is effective for chronic pain. 15 35 Consequently, a number of health policy and practice-oriented guidelines have been issued that support the use of acupuncture for chronic pain. For example, the American College of Physicians Clinical Practice Guideline recommends acupuncture for acute, subacute, and chronic low back pain (cLBP).…”
Section: Introductionmentioning
confidence: 99%
“…A substantial body of evidence demonstrates that acupuncture is effective for chronic pain. 15 35 Consequently, a number of health policy and practice-oriented guidelines have been issued that support the use of acupuncture for chronic pain. For example, the American College of Physicians Clinical Practice Guideline recommends acupuncture for acute, subacute, and chronic low back pain (cLBP).…”
Section: Introductionmentioning
confidence: 99%
“…In three of the five patients, the pain relief was immediate, and in all patients the vocal fold motion normalized. The authors equated the observed pain relief from LEMG to dry needling in the treatment of myofascial pain syndrome (MPS) . Dry needling at trigger points is thought to work through a hyperstimulatory analgesic effect.…”
Section: Discussionmentioning
confidence: 99%
“…The authors equated the observed pain relief from LEMG to dry needling in the treatment of myofascial pain syndrome (MPS). [7][8][9] Dry needling at trigger points is thought to work through a hyperstimulatory analgesic effect. Jung et al 6 suggested that pain can limit the range of vocal fold motion due to guarding, with hypomobility exacerbating the dysphonia.…”
Section: Primary Odynophoniamentioning
confidence: 99%
“…In 2017, Espejo-Antúnez et al published a SR that evaluated the clinical efficacy of dry needling to alleviate pain associated with myofascial trigger points (15 RCTs [106]) and found a possible short-term benefit following dry needling. In 2017, SRs have found tentative evidence that acupuncture alone or combined with other therapies improved outcomes associated with myofascial pain syndrome (10 RCTs [108]; 33 RCTs [107]), although substantial heterogeneity and a high risk of bias, including inadequate sample sizes in the primary RCTs, undermined confidence in the findings.…”
Section: Myofascial Pain Syndrome and Myofascial Trigger Pointsmentioning
confidence: 99%